Captives or Slaves? A Comparison of Northeastern and Northwestern North America by Means of Captivity Narratives - Donald, Leland (Culture)

(untitled) (Canadian Anthropology Society / Société Canadienne d’Anthropologie (CASCA), formerly/anciennement Canadian Ethnology Society / Société Canadienne d’Ethnologie, 1985)
Low status captives were present in many traditional North American Indian societies. This paper explores whether it is appropriate, in some of these societies, to label such captives as “slaves.” In particular, captivity is compared in the Northwest Coast and in the Northeast. To improve comparability of data, narratives of Europeans held captive in each region are compared, specifically those of John Gyles and John Jewitt. It is concluded that in the Northeast it is best to speak of “captives,” while on the Northwest Coast one can speak of “slaves.”